On piecewise interpolation techniques for estimating solar radiation missing values in Kedah - Saaban, Azizan; Zainudin, Lutfi; Abu Bakar, Mohd Nazari (2014)
This paper discusses the use of piecewise interpolation method based on cubic Ball and Bézier curves representation to estimate the missing value of solar radiation in Kedah. An hourly solar radiation dataset is collected at Alor Setar Meteorology Station that is taken from Malaysian Meteorology Department.The piece wise cubic Ball and Bézier functions that interpolate the data points are defined on each hourly intervals of solar radiation measurement and is obtained by prescribing first order derivatives at the starts and ends of the intervals We compare the performance of our proposed method with existing methods using Root Mean Squared Error (RMSE) and Coefficient of Determination (CoD) which is based on missing values simulation data sets. The results show that our method is outperformed the other previous methods.